Decomposition Analysis of Output Change under New Wheat Technology in Arid Region of Rajasthan: An Econometric Study - Gawaria, K M; Gajja, B L; Pathak, Rakesh (Annals of Arid Zone, 2016)
Wheat is one of the most important food grains known for various uses throughout the world. Introduction of modern technology in this crop has immense advantage. Production response functions for both the modern and traditional technology were estimated to understand the advantage of modern technology over traditional technology. The primary data were collected from 40 farmers each adopting modern and traditional technology in the IVLP villages in Osian Tehsil of Jodhpur District. The field demonstration method was used. The estimated farm level production response functions were significant and the upward shift in the production function due to technological improvement was through a shift in the intercept to the extent of 22%. The total difference in the productivity between modern and traditional wheat technology was estimated to be about 62%. The modern technology of wheat increased the production by 62.30% over the traditional variety. The technical contribution of modern wheat technology is about 46.45 and the remaining 14.22 was of more use of complementary inputs. The major component of this productivity gap was the difference in varietal technology contributing nearly 46%, while remaining 14% was shared by complementary inputs in terms of use levels between the modern and traditional wheat production technology. Key words: Wheat, production function approach, yield decomposition model, nature of technology change